Advanced Silicon Modeling of Native Mitral Valve Physiology: A New Standard for Device and Procedure Testing - Katell Delanoë; Erwan Salaun; Régis Rieu; Nancy Côté; Philippe Pibarot; Viktória Stanová (Bioengineering)
Mitral valve regurgitation is among the most prevalent valvular heart diseases and increases with age. Percutaneous therapy has emerged for the management of mitral regurgitation in high surgical risk patients. However, the long-term consequences of these interventions are still not fully understood due to their novelty and the difficulty of developing a strategy specific to the patient’s anatomy and/or pathology. To optimize these outcomes, an in vitro patient-specific approach could provide important insights for the most suitable strategy to use according to the patient profile. To ensure the reliability of this in vitro approach, the aim of this study was to reproduce the physiological behavior of the healthy native mitral valve for future applications. To do so, different silicon combinations reproducing the physiological anatomy of a healthy mitral valve were developed and tested under physiological hemodynamic conditions in a cardiac simulator. The hemodynamic and biomechanical behaviors of each mitral valve model were analyzed and compared to the physiological values provided in the literature. This study identified EcoFlex 00-50 and DragonSkin 10 (Smooth-On Inc., Easton, PA, USA) as the optimal silicon combination resulting in physiological strain values and hemodynamic parameters. These findings could be useful for future patient-specific applications, helping in the optimization of percutaneous mitral valve therapy.